A Perceived Divide : How Indonesians Perceive Inequality and What They Want Done About It - World Bank (World Bank, Jakarta, 2016)
Inequality in Indonesia is rising and a recent survey suggests that Indonesians are growing increasingly concerned. The Gini coefficient in Indonesia has increased sharply over the past 15 years, increasing from 30 in 2000 to 41 in 2013. In a 2014 survey on public perceptions of inequality, most Indonesians consider income distribution in Indonesia to be very unequal or not equal at all. In addition, half of all respondents feel that Indonesia has become more unequal or much more unequal over the past five years. The true extent of high inequality, however, is worse than most people realize. Respondents believe that the ideal income distribution is one where the top 20 percent of the population earn as much as the bottom 40 percent. Not with standing this ideal, respondents estimate that the actual income distribution has the top 20 percent earning as much as the bottom 60 percent. However, the 2014 National Socio-economic Survey (Susenas 2014) suggests that the richest 20 percent actually earn as much as the rest of the population combined. Furthermore, because household surveys typically do not capture the incomes of the richest Indonesians, the real level of inequality in Indonesia is probably even higher.